A thermal–metallurgical model of laser beam welding simulation for carbon steels. (April 2015) - Mi, Gaoyang; Zhan, Xiaohong; Wei, Yanhong; Ou, Wenmin; Gu, Cheng; Yu, Fengyi
Abstract A coupled thermal–metallurgical model is developed to predict the temperature fields and spatial distribution of volume fraction of phases during laser beam welding of 1020, 1045, and 1060 steels. The classical transient heat conduction model is used to calculate the temperature fields during laser beam welding. For phase transformation, the austenization, the austenite-to-pearlite/ferrite transformation, the austenite-to-bainite transformation, and the austenite-to-martensite transformation are modeled respectively. All of these transformation models are solved by the finite element method (FEM) based on the simulated temperature fields. The thermal properties of the three steels are determined by the linear interpolation base of the phase fractions, and thermal properties for each pure phase. The temperature fields and spatial distribution of phases are predicted by 3D finite element method (FEM) code which is developed by the authors to solve the thermal–metallurgical models. In addition, comparison between the coupled model and the pure conduction model without considering phase transformations is carried out to study the influence of phase transformation on temperature fields during welding. According to the comparison, the temperature of the coupled model is higher than the pure conduction model in the temperature region above 1000 °C, but the temperature profiles are very similar at the temperature region under 1000 °C. The predicted volume fractions of 1020 and 1060 steels are close to experimental results. However, there is an obvious difference between predicted and experimental results of the phase fraction of 1045 steels.